Examining the association between emotional intelligence with depression among Iranian boy students - Abdollahi, Abbas; Hosseini, Seyedeh Maryam Ebadi Nezhad; Motalebi, Seyedeh Ameneh; Abu Talib, Mansor (Leena & Luna International (Pvt) Limited, 2013)
The present study sought to examine the association between emotional intelligence and depression in boy students in, Tehran, Iran. The sample size was 188 boy students at the age of 16 to 19 years old were chosen for this study. The Assessing Emotions Scale (AES), and Beck Depression Inventory-II (BDI-II) were filled out by students. The Pearson correlation coefficient and multivariate regression analysis were utilized. The findings showed that a negative association existed between high ability of emotional intelligence with depression and a positive association existed between low ability of emotional intelligence with depression. These results revealed that emotional intelligence was a valuable predictor of depression in adolescents.